Brand Hate dan Negative Electronic Word of Mouth Terhadap Non-Purchase Intention - Yohana Mounthema Karina; Lingga Yuliana (Jurnal Ilmiah Global Education, 2026)
The purpose of this study is to examine the influence of Brand Hate and Negative Electronic Word of Mouth on Non-Purchase Intention, using a case study of the Baked n Grind brand. Quantitative research was used in this study. The sampling technique used was purposive sampling. A total of 154 respondents residing in Greater Jakarta (Jabodetabek) aged 17-50 years were involved in this study. The study was conducted in November 2025. Respondents were men and women who were consumers of bread and bakery products, social media users, and familiar with the latest information about the Baked n Grind brand. The data source used primary data by distributing questionnaires through Google Forms. The data analysis technique used Partial Least Squares with the SmartPLS data processing tool version 4.1.0.0. The first hypothesis indicates a positive and significant influence of Brand Hate on Non-Purchase Intention. Meanwhile, the second hypothesis indicates a positive but insignificant influence of Negative Electronic Word of Mouth on Non-Purchase Intention. This confirms that managing customer experience and consumer emotions is key to maintaining purchase intention. Baked n Grind needs to identify and address the sources of brand hate, such as inconsistent product quality, poor service interactions, or perceived unfairness. Preventive efforts are more important than remedial measures once hate has formed, as brand hate is difficult to reverse and directly impacts purchase decisions.